Enhanced procedures for mosquito identification by MALDI‑TOF MS - Bamou, Roland (2022)
Aix‑Marseille Univ., IRD, SSA, AP-HM, VITROME. Marseille, France / IHU Méditerranée Infection. Marseille, France.